Factors Influencing the Adoption of Multi Factor Authentication in the Public Sector: A Case Study of Indonesia National Single Window Agency - Purnomo, Dencaswo; Ghaisani, Amanda; Sensuse, Dana Indra; Lusa, Sofian; Ramlan, Nurcholis; Indrawati, Nur (AI Society & STMIK Indonesia, 2026)
This study aims to examine the factors that influence the intention and actual use of Multi-Factor Authentication (MFA) in the National Single Window Agency (LNSW). The research model integrates the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) with the addition of the Perceived Security (PS) construct. Data were collected from employees and vendor teams at the LNSW and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that Perceived Ease of Use (PEOU) and Social Influence (SI) have a positive and significant effect on Behavioral Intention (BI). In addition, Perceived Security (PS) does not have a direct effect on Behavioral Intention, but it has a significant positive effect on Perceived Usefulness (PU). Other findings show that Behavioral Intention (BI) is a strong predictor of Actual Usage (AU) of MFA. These results confirm the relevance of the TAM and UTAUT models in explaining the adoption of security technology in the public sector, and emphasize the importance of ease of use and organizational influence in encouraging the adoption of MFA